Impact of using metallized iron ore pellets to increase the efficiency of electric arc furnace - Ludmila N. Krakht; Edward E. Merker; Alexander Y. Kem; Victor A. Stepanov (Advanced Engineering Research)
The work objective is to determine the effect of the metallurgical properties of iron-rich pellets and of the method of their submission to the arc furnace bath on the intensification of the heating and melting of the iron metallized pellets (IMP) in the slag-metal melt unit. A method of supplying pellets through the electrode axial passages that allows, simultaneously with the pellets, feeding supplementary bulk materials (lime, coke fines, scale, etc.) to the IMP melting zone through the holes in the electrodes is offered. Thus, the conditions of the full immersion of the arcs into the formed foaming slag are provided. The effect of iron oxides of various phase and chemical compositions on the plastic properties of pellets is investigated. It is found that the microstructure invariance of fluxed pellets including the bonded phase composition is determined by the level of fluxing and the difference of the iron valent states. Improvement in the efficiency of IMP melting is achieved by feeding pellets with improved physicochemical and technological properties, as well as supplementary materials, into the slag-metal bath through the axial passages of the electrodes.